Great escape - Egan, Kate; Lane, Mike (Egan, Kate. Magic shop., 2014)
Mike is doing better in school these days. Learning magic helps him to learn other things as well. Sure, he's gotten in trouble in the past, but things are different now. So why does everyone still think he's the same old Mike? If only there was a magic trick to change his reputation...Then, during one of his visits to The White Rabbit Magic Shop, Mike finds something that could be even better than a magic trick - it's possible that Mike could be related to Harry Houdini - the greatest magician ever! But when Mike lets the news slip, and Jackson Jacobs dares him to prove it, he knows that he's in the type of bind that only magic can help him escape!